2001
DOI: 10.1046/j.1460-9592.2001.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin Induced Polymorphic Ventricular Tachycardia with Normal QT Interval

Abstract: Polymorphic ventricular tachycardia (PVT) is a form of ventricular tachycardia characterized by QRS complexes that seem to change direction during the tachycardia. If associated with a prolonged QT interval, it is called torsades de pointes. In the absence of a congenital long QT syndrome, torsades is seen with certain drugs such as antiarrhythmic agents (Class IA, IC, III), psychotropic medications, antidepressants, antihistamines, and electrolyte disturbances. We report the first case of polymorphic ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Paltoo et al reported the first case of polymorphic ventricular tachycardia in response to the use of levofloxacin in patients with no risk factors [39]. Patel et al reported that polymorphic ventricular tachycardia occurred in a 91-year-old woman with flu-like symptoms after using levofloxacin [40].…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Paltoo et al reported the first case of polymorphic ventricular tachycardia in response to the use of levofloxacin in patients with no risk factors [39]. Patel et al reported that polymorphic ventricular tachycardia occurred in a 91-year-old woman with flu-like symptoms after using levofloxacin [40].…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Indeed, there are reported cases of TdP in patients with apparently normal QT interval. 92 To further complicate the issue, no standard exists even for QT measurement itself. 3 In collecting and analyzing electrocardiograms, one should consider the guidelines for electrocardiographic evaluation of drug-related QT prolongation and other alterations in ventricular repolarization from the International Society for Holter and Noninvasive Electrocardiology (ISHNE).…”
Section: B Clinical Studiesmentioning
confidence: 99%
“…One case of levofloxacin-associated torsades des pointes in the absence of QTc interval prolongation has also been reported [391]. Grepafloxacin was removed from the market by its manufacturer in October 1999 because of its electrophysiologic adverse event profile.…”
Section: Quinolones and Electrophysiologymentioning
confidence: 99%